Receptions of Hellenism in early modern Europe
1 online resource.
Keywords: This volume, edited by Natasha Constantinidou and Han Lamers, investigates modes of receiving and responding to Greeks, Greece, and Greek in early modern Europe (15th-17th centuries). The book's 17 detailed studies illuminate the reception of Greek culture (the classical, Byzantine, and even post-Byzantine traditions), the Greek language (ancient, vernacular, and 'humanist'), as well as the people claiming, or being assigned, Greek identities during this period in different geographical and cultural contexts. Discussing subjects as diverse as, for example, Greek studies and the Reformation, artistic interchange between Greek East and Latin West, networks of communication in the Greek diaspora, and the ramifications of Greek antiquarianism, the book aims at encouraging a more concerted debate about the role of Hellenism in early modern Europe that goes beyond disciplinary boundaries, and opening ways towards a more over-arching understanding of this multifaceted cultural phenomenon. Contributors include Aslıhan Akışık-Karakullukçu, Michele Bacci, Malika Bastin-Hammou, Peter Bell, Michail Chatzidakis, Federica Ciccolella, Calliope Dourou, Anthony Ellis, Niccolò Fattori, Maria Luisa Napolitano, Janika Päll, Luigi-Alberto Sanchi, Niketas Siniossoglou, William Stenhouse, Paola Tomè, Raf Van Rooy, and Stefan Weise